2021
DOI: 10.1177/08971900211030248
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use and Associated Risk Factors for Antibiotic Prescribing in COVID-19 Hospitalized Patients

Abstract: Background: Literature suggests that antibiotic prescribing in COVID-19 patients is high. Currently, there are insufficient data on what drives antibiotic prescribing practices throughout the COVID-19 pandemic. Objective: This study sought to determine antibiotic use rates and identify risk factors for antibiotic prescribing in hospitalized patients. It was the first study to assess risk factors for receiving more than 1 course of antibiotics. Methods: This was a retrospective, multi-center, observational stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 23 publications
2
10
0
11
Order By: Relevance
“…In addition to the misuse of antibiotics among COVID-19 patients, our study provided an insight into the prescribing practises of clinicians which is relevant to the establishment of antimicrobial stewardship programmes in health care facilities. However, despite these worrying results, they are similar to reports from other countries in the African Region (47% in Kenya, 71% in South Africa, and 76% in Uganda) and elsewhere (78% in Spain, 83% in the USA, 100% in Bangladesh, and 67–90% in several studies from China) showing high use of antibiotics in COVID-19 patients [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. In contrast, a study from Singapore reported a very low level (~5%) of antibiotic use [ 40 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition to the misuse of antibiotics among COVID-19 patients, our study provided an insight into the prescribing practises of clinicians which is relevant to the establishment of antimicrobial stewardship programmes in health care facilities. However, despite these worrying results, they are similar to reports from other countries in the African Region (47% in Kenya, 71% in South Africa, and 76% in Uganda) and elsewhere (78% in Spain, 83% in the USA, 100% in Bangladesh, and 67–90% in several studies from China) showing high use of antibiotics in COVID-19 patients [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. In contrast, a study from Singapore reported a very low level (~5%) of antibiotic use [ 40 ].…”
Section: Discussionsupporting
confidence: 84%
“…The study from Spain reported that inappropriate antibiotic use was more likely in patients in the younger age groups and in those without co-morbidities [ 36 ]. Similarly, a study from USA reported an association of antibiotic use with increased duration of hospital stay and with patients admitted to ICU and needing mechanical ventilation [ 37 ]. In contrast, we did not find any association between the duration of a hospital stay and antibiotic use.…”
Section: Discussionmentioning
confidence: 99%
“…Independent factors that affect the decision of a physician in prescribing an antibiotic include advanced age, presence of comorbidity, February–March 2020 admissions, symptoms of dry cough, fever, dyspnoea, flu-like, and elevated C-reactive protein (CRP) biomarkers [ 4 , 12 ], procalcitonin [ 11 ], long hospital length of stay with a median of 12 days, admission to the ICU, and the necessity for mechanical ventilation [ 13 ]. Given variations in the management of COVID-19 in different countries, where some countries admit all COVID-19 patients while others only admit patients with severe symptoms, the factors affecting the use of antibiotic agents could be varied and influenced by the health policy that is unique to each country.…”
Section: Introductionmentioning
confidence: 99%
“…In the 75.8% of the coinfected group that required supplementary oxygen, only about 50% of them received systemic corticoids; some cases were because they were hospitalized before this treatment indication was supported by the recovery trial data (22). Another treatment (23,24). Two patients of the coinfected cohort in the ICU received convalescent human plasma and ivermectin as compassionate treatment; these treatments are not currently indicated, but compassionate treatments are expected to change dynamically during any new and severe disease, such as the COVID-19 pandemic, before evidence support them or not (25)(26)(27).…”
Section: Discussionmentioning
confidence: 93%